Making School Development Credible: Text, Context, Irony - Börjesson, Mats (Scandinavian Journal of Public Administration, 2011)
The article argues for the importance of an open, reflexive-methodological approach when switching between studying text, context and researcher activity. Close linguistic analysis can benefit from being linked with the researcher’s contextualisation of his empirical material as well as with more distanced readings. The more specific starting point for this article is that school development, like other similar terms such as school improvement and the like, makes use of linguistic building blocks with which whole narratives about today’s and tomorrow’s schools can be constructed. The subject of the study is a short text issued by the Swedish Schools Inspectorate (Skolinspektionen). Government language changes according to the authorities’ role in society and their own definitions of their functions, and an important aspect here is the legitimacy of the authorities’ texts. By means of various kinds of close linguistic analysis, the above-mentioned text is studied with regard to choice of categories, hierarchies of modalisation and the rhetorical effects of different types of formulations in a broader political-social landscape. The article concludes with a reflective discussion on the relationship between government language and irony as a stylistic device – a device that is based on the results of the close empirical analysis.1